Comprehending Terms Through Contexts - Abdinazarov Xasan Shaymanovich (Scientific Trends, 2025)
In the recent years, a lot of changes have been made in education system, especially in the educational life of learners. Their wish of using innovative technology fulfilled their dreams in studying unknown words during the English for petroleum engineering. Besides, they decided to use more electronic applications in understanding the technical context in the English and Uzbek languages. This paper outlines the effectiveness of electronic dictionaries in English for petroleum engineering classes and their use consequently, the influence of terminology for text-comprehension in subject-specific issues. The examples of terminology for Petroleum engineering are provided.
Keywords: Dictionary, ESP classes, terminology.